The profiling and identification of chemical components, prototypes and metabolites of Run‐zao‐zhi‐yang capsule in rat plasma, urine and bile by an UPLC‐Q‐TOF/MSE‐based high‐throughput strategy. (31st May 2018) - Lin, Shan; Yue, Xinyi; Ouyang, Danwei; Li, Quan; Yang, Peiming
Abstract: Run‐zao‐zhi‐yang (RZZY) capsule, a traditional Chinese medicine formula, is popularly used for the treatment of dermatitis and eczema. However, few studies have been carried out on RZZY and its metabolites. In this study, we developed a three‐step strategy to rapidly characterize the chemical constituents and metabolites of RZZY using ultra‐high‐performance liquid chromatography coupled with quadrupole time‐of‐flight mass spectrometry. A total of 41 chemical components were characterized from RZZY. Among these, there are 11 flavonoids, six alkaloids, six stilbene glycosides, five anthraquinones and 13 other compounds. In addition, 18 prototypes and 35 metabolites were detected in rat plasma, urine and bile. This study offers an applicable approach for high‐throughput profiling and identification of chemical components and metabolites derived from traditional Chinese medicine formula in vivo, and also provides essential data for exploring bioactive ingredients and action mechanisms of RZZY.